2009
DOI: 10.1111/j.1748-0159.2009.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Silicone poaching pods: do they meet manufacturer's claims?

Abstract: Manufacturers are marketing silicone cooking and baking devices (e.g. cake pans) for a variety of foods, and claim these devices are easy to use, stick‐resistant, heat‐resistant, stain‐resistant and dishwasher‐safe. Recent research has reported contrary results from the manufacturers' claims. Silicone Poaching Pods were tested in this study to determine if they are as effective as claimed by manufacturers. Results indicated that in fact Poaching Pods are not easy to use. Egg products stuck to the pods during p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…A study by Barber et al (2007) found that traditional metal cake pans produce a product that releases easily from the pan, while the silicone cake pans would not release their product, resulting in damaged finished products. In another study, Barber et al (2009b), found that silicone egg‐poaching pods produce an inferior product to that of the traditional method of poaching. The finished egg product would not release easily from the poaching pod, and the pods often capsized in the cooking vessel.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Barber et al (2007) found that traditional metal cake pans produce a product that releases easily from the pan, while the silicone cake pans would not release their product, resulting in damaged finished products. In another study, Barber et al (2009b), found that silicone egg‐poaching pods produce an inferior product to that of the traditional method of poaching. The finished egg product would not release easily from the poaching pod, and the pods often capsized in the cooking vessel.…”
Section: Introductionmentioning
confidence: 99%